2007
DOI: 10.1534/genetics.107.075176
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Pattern of a Rice Disease Resistance Gene Xa3/Xa26 Is Differentially Regulated by the Genetic Backgrounds and Developmental Stages That Influence Its Function

Abstract: Genetic background and developmental stage influence the function of some disease resistance (R) genes. The molecular mechanisms of these modifications remain elusive. Our results show that the two factors are associated with the expression of the R gene in rice Xa3 (also known as Xa26)-mediated resistance to Xanthomonas oryzae pv. oryzae (Xoo), which in turn influences the expression of defenseresponsive genes. The background of japonica rice, one of the two major subspecies of Asian cultivated rice, facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 40 publications
6
111
0
1
Order By: Relevance
“…For example, Xa26 was isolated from the indica cultivar Minghui 63 (58), where it confers moderate resistance against bacterial blight at seedling and adult stages. When this gene was introduced into several japonica cultivars with its native promoter, transgenic plants showed enhanced resistance, featuring broadened resistance spectrum and increased resistance level in extended growth stages (73). It was shown that the enhanced resistance is closely associated with the elevated expression of the gene.…”
Section: Identification Of Genes For Disease Resistance and Developmementioning
confidence: 99%
“…For example, Xa26 was isolated from the indica cultivar Minghui 63 (58), where it confers moderate resistance against bacterial blight at seedling and adult stages. When this gene was introduced into several japonica cultivars with its native promoter, transgenic plants showed enhanced resistance, featuring broadened resistance spectrum and increased resistance level in extended growth stages (73). It was shown that the enhanced resistance is closely associated with the elevated expression of the gene.…”
Section: Identification Of Genes For Disease Resistance and Developmementioning
confidence: 99%
“…Scott et al (1998) have claimed that allelic composition and genetic background affect transgene expression and inheritance in white clover. Another study in rice showed that the expression pattern of Xa3/Xa26, which is a rice disease resistance gene, was affected by the genetic background (Cao et al 2007). The full effects of gene dosage and genetic background on transgene expression and translation remain to be elucidated.…”
mentioning
confidence: 99%
“…Nevertheless, significant induction of R gene expression during the plant defence response also occurs in certain cases (Yoshimura et al, 1998;Halterman et al, 2003;Levy et al, 2004;Gu et al, 2005;Cao et al, 2007;Mohr et al, 2010). There are examples of increasing the expression of an R gene converts HR to ER suggesting that the level of R protein regulates the strength of resistance to a virus.…”
Section: Genes Associated With Er Type Resistancementioning
confidence: 99%